Modelling the ways to increase the creativity of psychology students as a basic factor in professional development - Kryshtanovych, Myroslav; Bilyk, Valentyna; Hanushchyn, Solomiia; Sheremet, Inesa; Vasylenko, Kateryna (Creativity Studies, 2021)
One of the important tasks of the modern system of psychology in higher educational institutions is not only the development of student’s professional potential but also the comprehensive development of their personality. The purpose of the article is to systematize the process of increasing the creativity of psychology students with the help of mechanisms and elements of the functional model of IDEF0. The novelty of this study lies in the fact that in the field of education, in particular, increasing such a subjective indicator as creative abilities, there has not yet been a methodology that allows forming an understandable and simple, but at the same time flexible system of actions. The reason for choosing this model was that it is the most visual and easy to understand for representatives of higher educational institutions. Also, this model is universal in terms of adding separate sublevels and subtasks, if for a particular educational institution it turns out to be incomplete or insufficiently detailed. Thus, it is the IDEF0 model that can reveal to the greatest extent such a subjective process as an increase in creativity among psychology students. The steps for increasing the creativity of psychology students are presented, which are the result of scrupulous analysis and many years of research by the authors in this area. The scientific contribution of this article can be considered the formation of a mechanism for increasing the creativity of psychology students, not in the context of creating a clear methodology, but in the context of forming a universal algorithm with poly-levels for detailing the goal.